Three new species of mites in the genus Castriidinychus Hirschmann from Tasmania (Acari: Uropodidae) - Dylewska, M.; Błoszyk, J.; Halliday, R. B. (Zootaxa, 2010)
Three new endemic Tasmanian species of mites in the genus Castriidinychus Hirschmann are described (Acari: Uropodidae). These species are clearly different from those previously described from the Australian mainland. Castriidinychus tasmanicus sp. nov. was found at a number of localities in northern and western Tasmania, and C. longisetosus sp. nov. was more frequent in the east. The rarest species, C. robynae sp. nov. was recorded only at three localities in the southeastern part of the island. The confused taxonomic history of the genus Castriidinychus is reviewed and clarified.